2012
DOI: 10.1111/j.1399-3046.2012.01672.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance imaging in children with chronic kidney disease and renal transplantation

Abstract: CV disease is the major cause of death in patients with CKD. Recently, CMR imaging emerges as a complementary method providing advantages in cardiac assessment; however, data on CMR in pediatric CKD are scarce. We performed CMR in 15 children: two with CKD, six on peritoneal dialysis, seven on hemodialysis, and in 18 children 5.1 (0.4-15.4) yr after kidney Tx. Eight children underwent CMR six months before and after Tx. Results are presented as mean z score ± SD. LV EF was higher and in the normal range in Tx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Dear Editor, "Cardiac magnetic resonance imaging in children with chronic kidney disease and renal transplantation," a report by Schaefer et al, deals with the problem of uremic cardiomyopathy in children with stage two chronic kidney disease (CKD) (1). Cardiovascular impairments in patients with CKD may be extremely detrimental, with a considerable percentage of fatal outcomes.…”
mentioning
confidence: 99%
“…Dear Editor, "Cardiac magnetic resonance imaging in children with chronic kidney disease and renal transplantation," a report by Schaefer et al, deals with the problem of uremic cardiomyopathy in children with stage two chronic kidney disease (CKD) (1). Cardiovascular impairments in patients with CKD may be extremely detrimental, with a considerable percentage of fatal outcomes.…”
mentioning
confidence: 99%
“…In children, CMR imaging is routinely used in the evaluation of cardiac anatomy and function in patients with congenital heart disease, and additional uses for CMR imaging in pediatrics have been recently described. Schaefer and colleagues reported that kidney transplant in children is associated with significant improvement in cardiac structure and function by CMR imaging. CMR imaging could also play a potentially useful role in the early detection and monitoring of cardiac dysfunction in children and young adults on maintenance dialysis .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that CMR imaging has potential disadvantages . It is not widely available and is more expensive and the duration of a cardiac assessment can be longer compared with ECHO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMR yields high-quality images across the entire left ventricle that is not impeded by thoracic fat deposits and chest wall expansion. Furthermore, CMR is used in the evaluation of congenital heart disease, ant its use has been recently reported in children and young adults on maintenance dialysis (17, 18), and renal transplant recipients (19). Our group has described the utility of CMR in overweight hypertensive children and reported reproducibility (20).…”
Section: Detection Methodsmentioning
confidence: 99%